Minority Inflation, Unemployment, and Monetary Policy - Munseob Lee; Claudia Macaluso; Felipe Schwartzman (Institute of Labor Economics (IZA), 2024)
Our paper addresses the heterogeneous effects of monetary policy on households of different races. The cyclical volatility of real income differs significantly for households of different races and income levels, reflecting differential exposure to fluctuations in employment and consumer prices. All Black households are disproportionately affected by employment fluctuations, whereas price volatility is only particularly pronounced for Black households with income above the national median. The latter face 40 percent higher price volatility than both poorer households of the same race and white households of similar income. To evaluate the effects of policy, we propose a New Keynesian framework with heterogeneous exposure to employment and price volatility. We find that an accommodative monetary stance generates asymmetric outcomes within race groups. Low-income households experience unemployment stabilization benefits, while high-income ones incur real income volatility costs. Differences are especially large among Black households. Reducing the volatility of unemployment by 1 percentage point engenders a 1.17 percentage point reduction in overall income volatility for poorer Black households, but an increase of 0.6 percentage points in income volatility for richer Black households.
Keywords: E31; E52; J15; 330